Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1741-3737.2009.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

The Social Relations Model in Family Studies: A Systematic Review

Abstract: The Social Relations Model (SRM) allows for examination of family relations on three different levels: the individual level (actor and partner effects), the dyadic level (relationship effects), and the family level (family effect). The aim of this study was to present a systematic review of SRM family studies and identify general patterns in the results. Results of reanalyses of 17 data sets showed that characteristics of the person who reports on the relationship and the unique characteristics of the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
94
3
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(123 citation statements)
references
References 35 publications
20
94
3
3
Order By: Relevance
“…As described above, family effects were of substantive interest. Moreover, the review by Eichelsheim et al (2009) suggests that partner variances are often modest. Presently, exploratory analyses revealed partner variances and generalized reciprocity correlations that were not significantly different than zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described above, family effects were of substantive interest. Moreover, the review by Eichelsheim et al (2009) suggests that partner variances are often modest. Presently, exploratory analyses revealed partner variances and generalized reciprocity correlations that were not significantly different than zero.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the present study employed a single indicator for each directed relationship, preventing the separation of true relationship variance from measurement error. The high internal consistency of CS and analyses by Eichelsheim et al (2009) suggest that results would be the same if multiple indicators were available. Moreover, in terms of unaccounted measurement error, the relationship variances in the present study would be overstated and the relative importance of family and actor variances (which were found to be sizable and significant) would be understated.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Eichelsheim et al (2009) found that, averaged over studies, the actor effects generally explain the largest proportion of variance in the influence domain. Finding substantial actor variance for mothers, implies that some mothers experience more influence towards all family members than other mothers in other families.…”
mentioning
confidence: 99%
“…Since the behavior of one person within a family has consequences that go beyond that one individual (Cook, 2005) it is recommended to investigate the family functioning in its full complexity. The parent-child relationship for example is a specific dyad within a family as a whole and should not be viewed in isolation (Eichelsheim, Deković, Buist, & Cook, 2009). …”
mentioning
confidence: 99%